Falhas e complicações com o uso de prótese parcial removível inferior de extremidade livre bilateral - Tôrres, Ana Clara Soares Paiva (2014)
Aim: To determine the frequency and type of complications related to removable partial denture (RPD) less, Kennedy Class I, over time . Materials and Methods: This observational study consisted of a sample of 65 users PPR lower arches in Kennedy Class I and dentures, rehabilitated in the Department of Dentistry, Federal University of Rio Grande do Norte (UFRN). Patients were followed through periodic controls during periods of 60 days, 6 months and 1 year from installation. After the first year of control had other returns annually. The occurrence of complications or prosthetic failure was observed and recorded in a specific clinical record over 39 months. The patterns of failures observed were classified in the following situations: occurrence of traumatic ulcers after 2 months of installation, lack of retention, fracture or caries in the rest, fracture or dislocation of the artificial teeth, the larger connector fracture, fracture clip fracture support, poor support (need to reline the denture) and prosthesis fracture. Results: The incidence of complications was low frequency, being higher in the second year of use of the prosthesis. Among the complications that occurred more is the loss of retention (31.57%). Failures more severe and difficult to solve as the fracture elements of the metal structure of the PPR had low occurrence and were represented by only one case of the larger connector (5.3%) fractures. Conclusion: Removable partial dentures mandibular free end opposing of the conventional dentures have a low complication rate after 39 months of use when subjected to periodic controls